High-throughput molecular identification of Staphylococcus spp. isolated from a clean room facility in an environmental monitoring program - Amin Magdy A; Yassin Aymen S; Sheraba Norhan S (BMC Research Notes, 2010)
Abstract Background The staphylococci are one of the most common environmental isolates found in clean room facility. Consequently, isolation followed by comprehensive and accurate identification is an essential step in any environmental monitoring program. Findings We have used the API Staph identification kit (bioMérieux, France) which depends on the expression of metabolic activities and or morphological features to identify the Staphylococcus isolates. The API staphylococci showed low sensitivity in the identification of some species, so we performed molecular methods based on PCR based fingerprinting of glyceraldehyde-3-phosphate dehydrogenase encoding gene as useful taxonomic tool for examining Staphylococcus isolates. Conclusions Our results showed that PCR protocol used in this study which depends on genotypic features was relatively accurate, rapid, sensitive and superior in the identification of at least 7 species of Staphylococcus than API Staph which depends on phenotypic features.